Benefits of physical activity in aging - Martins Vilela, Ana Paula; Pereira Coelho, Marta; Nunes Moraes Partelli, Adriana; Romais Schmildt, Edilson; Costa Velten, Ana Paula; Gripa Barcellos dos Santos, Ludmilla; Medani Tristão, Kamila (Guará Journal, 2025)
This cross-sectional study was conducted among physically active older adults participating in the "Happy Age" Extension Project and sedentary older adults. The aim was to compare the blood glucose, cholesterol, and anthropometric data of sedentary older adults with those of active older adults. Data collection was performed through blood and anthropometric tests, and significant differences were found in the variables total cholesterol, LDL cholesterol, systolic blood pressure, heart rate, and respiratory rate between active and sedentary older adults. The conclusion was that regular physical activity among older adults significantly improved total and LDL cholesterol levels, systolic blood pressure, and heart and respiratory rate.
Keywords: Happy age; Aging; Physical Activity